Android-based sports competition scheduling system - Ma, Teng (2015)
This report is about building a mobile-based single round-robin sports scheduling system with heuristic methods. Based on the current meta-heuristic methods in sports scheduling, this work did further researches on applying the current algorithms to a mobile platform while guarantee the quality and efficiency. Besides, a new system with the ability to deal with all the possible situations in practical use is proposed. Moreover, a simple user interface is built for the application.